Teater GloBALIsme: Pariwisata, Interkoneksi Global, dan Nasib Manusia Bali di Garis Depan - I Ngurah Suryawan (Pusat Kajian Bali Universitas Udayana, 2011)
AbstractThe development of the tourism industry in Bali has had various implications.Apart from extraordinary social change, there is the issue of how Balinese menstruggle to maintain their cultural identity in the midst of globalized tourism.Balinese men are at the frontier of a society where global powers meet to exploitnatural and human resources for the sake of tourism. Some Balinese men havelost their historical relationship to Bali because their own land has been sold toinvestors. Origin and identity maintenance are no longer directed to the land orto certain communities, but rather to a never-never land, a (global) world withoutmeaning that one is no longer able to localize (Laksono, 2009b). It is in this neverneverspace without meaning that we witness fragments and stories of Balinesemen making use of opportunities, developing tactics, and even fighting againsttourism, which Tsing (2005) has called friction. In this so-called friction, localidentity and culture are continually reproduced, the beginning and end of whichare difficult to fathom.